Study and optimization of swimming performance in swimsuit designed with seamless technology - Montagna, Gianni (2009)
Hydrodynamic resistance, also called water drag, is one of the most discussed issues in swimming sport and recognized as a major factor in terms of swimming performance. Different authors tried to demonstrate that body compression is responsible for a better result in swimming, based on the fact that body modelling improves energy saving and helps to maintain the performance on repetitive movements. In this paper, different weft knitted fabrics, prepared under predefined production parameters, were tested in order to establish which were the most adequate for compressive effect and which parameters contribute most for compression.